Sociedad de la Información: uso de la Web 2.0 por comunicadores politicos brasileros - Castanheira, Karol Natasha Lourenço [UNESP]; Vicente, Maximiliano Martin [UNESP] (My University, 2011)
The social spread of vectors of technological acceleration in daily life and the effects of modernization, in some way, attributed to the media a primary importance as the axis of symbolic mediation, and its role socially recognized and legitimized. In politics, some of these effects are essential for the exhibitionism and visibility of political communicator. This process intensifies with new technologies that open up space in a still uneven way, but very interactive between citizens and political actors. This process intensifies with new technologies that open a space between citizens and political actors unevenly, but very interactive. The aim of this paper is to analyze the use of the Internet, through social networks, by Brazilian politicians, especially, the former candidate for president, by the Green Party, Marina Silva. The methodology of analysis is the virtual ethnography, which part of a dialectical view ofculture, in which it moves between social structures and social practices of historical subjects.

La propagación social de vectores de aceleración tecnológica en la vida cotidiana y los efectos de la modernización, atribuyeron de cierta forma, a los medías importancia fundamental como eje de mediación simbólica, teniendo su papel socialmente reconocido y legitimado. En la política, algunos de estos efectos se dan por la necesidad de exhibicionismo y visibilidad del comunicador político. Este proceso se intensifica con las nuevas tecnologías, que abren espacio, de forma aún desigual, pero bastante interactiva, entre los ciudadanos y los actores políticos. El objetivo de este artículo es analizar el uso dado internet a través de las redes sociales por los políticos brasileños, especialmente la ex-candidata a presidente de la República por el Partido Verde, Marina Silva. La metodología de análisis es la etnografía virtual o netnografia, que parte de una visión dialéctica de la cultura, en la cual esta se mueve entre las estructuras sociales y las prácticas sociales de los sujetos históricos.
Keywords: Politic; New technologies; Virtual ethnography; Marina Silva; Modernization; Política; Nuevas tecnologías; Etnografía virtual; Marina Silva; Modernización